Epilepsy miRNA Profile Depends on the Age of Onset in Humans and Rats - Baloun, Jiri; Bencurova, Petra; Totkova, Tereza; Kubova, Hana; Hermanova, Marketa; Hendrych, Michal; Pail, Martin; Pospisilova, Sarka; Brazdil, Milan (Frontiers in Neuroscience, 2020)
Temporal lobe epilepsy (TLE) is a severe neurological disorder accompanied by recurrent spontaneous seizures. Although the knowledge of TLE onset is still incomplete, it is assumed that TLE pathogenesis involves aberrant expression of microRNAs (miRNAs). miRNAs play an essential role in organism homeostasis and are widely studied in TLE as potential therapeutics and biomarkers. However, many discrepancies in discovered miRNAs occur among TLE studies due to model-specific miRNA expression, different onset age of epilepsy among patients, or technology-related bias. We employed a massive parallel sequencing approach to analyse brain tissues from 16 mTLE/HS patients, 8 controls and 20 rats with TLE-like syndrome, 20 controls using the same workflow, and categorized these subjects based on the age of epilepsy onset. All categories were compared to discover overlapping miRNAs with an aberrant expression which could be involved in TLE. Our cross-comparative analyses showed distinct miRNA profiles across the age of epilepsy onset and found that the miRNA profile in rats with adult-onset TLE shows the closest resemblance to the profile in mTLE/HS patients. Additionally, this analysis revealed overlapping miRNAs between patients and rat model which should participate in epileptogenesis and ictogenensis. Among the overlapping miRNAs stands out miR-135a-5p, which regulates neuron development and reduces recurrent seizures. Our cross-comparison study enhanced the insight into the effect of the age of epilepsy onset on miRNA expression and deepened the knowledge of epileptogenesis. We employed the same methodological workflow in both patients and the rat model, thus enhancing the reliability and accuracy of our results.